Level Application of Farmers To Scientific Recommendations For The Corn Crop In Al-Hamdaniya District / Nineveh Governorate - Talal Hameed; Rayan Kadem; Ali Hameed; Anna Dadasiewicz (Mesopotamia Journal of Agriculture)
This research was carried out in Al-Hamdaniya district of Nineveh governorate, and this study aimed to identify the level of farmers’ application of scientific recommendations for the yellow corn crop in Al-Hamdaniya district / Nineveh governorate. Identify the level of yellow maize farmers’ application of scientific recommendations in the field of cultivation and service of the crop. As well as identifying the correlation between the level of farmers' application of the scientific recommendations for the yellow corn crop and each of the following independent factors (level of education, age, number of years of work in agriculture, cultivated land area, agricultural information sources). The research community included all the farmers of the yellow corn crop in the Al-Hamdaniya district, who numbered (188) farmers, a random sample of them was taken at a rate of (50%), and thus the total number of the respondents was (94). A questionnaire was prepared for the purpose of data collection. It consisted of two parts, the first included independent variables data related to the respondents, while the second part included a scale to measure the level of application of scientific recommendations by maize farmers. The results showed that more than half of the respondents were applying the scientific recommendations for the yellow corn crop at an average level. The results also showed that the variables (level of education, age and number of years of work in agriculture) had a significant correlation with the level of application of the scientific recommendations by maize farmers.